Transient testing of uranium silicide fuel in zircaloy and silicon carbide cladding. (15th September 2021) - Kamerman, David; Woolstenhulme, Nicolas; Imholte, Devin; Fleming, Austin; Jensen, Colby; Folsom, Charles; Woolum, Connor; Tritthart, Korbin; Schulthess, Jason; Wachs, Dan
Highlights: Transient irradiations of Uranium Silicide Fuel in Zircaloy and Silicon Carbide Cladding took place at the TREAT reactor at Idaho National Laboratory. The test rods maintained a "rod-like" or coolable geometry up to transient energy depositions of 528 J/g which should have been sufficient to cause local fuel melting based on the thermophysical properties of the Uranium Silicide Fuel. Abstract: Using the newly restarted Transient Reactor Test (TREAT) facility at Idaho National Laboratories, fresh (unirradiated) U3 Si2 fuel pellets were tested under reactivity-initiated accident conditions in dry helium capsules. These tests were performed with total energy depositions sufficient to induce melting of the U3 Si2 fuel pellets based on available thermophysical property data. The instrumented experiments utilized in-pile thermocouples and infrared pyrometers to measure the cladding temperature during the transient, which are in reasonable agreement with predicted peak cladding temperatures using a simple BISON fuel performance model. This same model is then used to predict expected cladding stresses during the transients in areas where pellet cladding interaction is expected. It was shown that for transient energy depositions up to 528 J/g rod like geometry of the test articles was maintained. While it is acknowledged that more confirmatory testing is required in more prototypic environments, these first of their kind experiments have demonstrated that unirradiated U3 Si2 fuel and unirradiated SiC-SiC claddings can likely retain a "rod like" geometry for transient energy depositions up to 528 J/g.